2020
DOI: 10.1002/open.202000144
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Side‐Chain Functionalities at Distinct Positions Determine the Chirooptical Properties and Supramolecular Structures of Pentameric Oligothiophenes

Abstract: Control over the photophysical properties and molecular organization of π‐conjugated oligothiophenes is essential to their use in organic electronics. Herein we synthesized and characterized a variety of anionic pentameric oligothiophenes with different substitution patterns of L‐ or D‐tyrosine at distinct positions along the thiophene backbone. Spectroscopic, microscopic, and theoretical studies of L‐ or D‐tyrosine substituted pentameric oligothiophene conjugates revealed the formation of optically active π‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 42 publications
5
10
0
Order By: Relevance
“…[38] A recent study of pentameric oligothiophenes functionalized with L-or D-tyrosine residues also showed that the location of the amino acid functionalities of the oligothiophene backbone had a great impact on the optical behaviour of the ligands, as ligands having tyrosine residues in the β-positions showed a greater pH-induced red-shifted absorption maximum compared to a ligand with tyrosine functionalities at the terminal αpositions. [32] Interestingly, when comparing HS-84-Y-Y with the previously reported p-FTAA-L-Tyr (SI, Figure S2), similar absorption and emission characteristics were obtained for both ligands in buffer pH 2, whereas in alkaline conditions (buffer pH 10) a slightly red-shifted absorption maximum and a blue-shifted emission spectrum were observed for HS-84-Y-Y (SI, Figure S2). From a chemical perspective, these ligands have both tyrosine functionalities at the terminal α-positions, but p-FTAA-L-Tyr is lacking the amino acid functionalities in the β-position of the thiophene moieties surrounding the central thiophene unit.…”
Section: Absorption and Emission Characteristicssupporting
confidence: 79%
See 3 more Smart Citations
“…[38] A recent study of pentameric oligothiophenes functionalized with L-or D-tyrosine residues also showed that the location of the amino acid functionalities of the oligothiophene backbone had a great impact on the optical behaviour of the ligands, as ligands having tyrosine residues in the β-positions showed a greater pH-induced red-shifted absorption maximum compared to a ligand with tyrosine functionalities at the terminal αpositions. [32] Interestingly, when comparing HS-84-Y-Y with the previously reported p-FTAA-L-Tyr (SI, Figure S2), similar absorption and emission characteristics were obtained for both ligands in buffer pH 2, whereas in alkaline conditions (buffer pH 10) a slightly red-shifted absorption maximum and a blue-shifted emission spectrum were observed for HS-84-Y-Y (SI, Figure S2). From a chemical perspective, these ligands have both tyrosine functionalities at the terminal α-positions, but p-FTAA-L-Tyr is lacking the amino acid functionalities in the β-position of the thiophene moieties surrounding the central thiophene unit.…”
Section: Absorption and Emission Characteristicssupporting
confidence: 79%
“…Thus, both the ICD pattern, as well as the intensity of the ICD, was influenced by the chemical nature of the amino acid sidechain functionalities and the positioning of the amino acid functionality along the conjugated thiophene backbone, verifying that distinct amino acid substitutions along the pentameric oligothiophene backbone had a substantial impact on the helical packing of the thiophene backbone. Similar ICD patterns have also been observed for tyrosine functionalized pentameric oligothiophenes, [32] as well as for zwitter-ionic polythiophenes having L-or D-serine in the β-positions. [24] However, for the latter, the ICDs were a result of main-chain chirality instead of aggregation.…”
Section: Induced Circular Dichroismsupporting
confidence: 74%
See 2 more Smart Citations
“…Finally, we put the supramolecular model structures to test by calculating the associated CD spectra and compare them against the experimental results. In our experience, CD spectra are very sensitive to the (supra)­molecular structure and even a successful qualitative comparison between theoretical and experimental spectra can provide strong evidence for the structure model to be sound. Supramolecular systems in general, and our nanotubes are no exception to this rule, are sufficiently dynamic at room temperature to mandate a configuration space sampling when performing CD spectrum simulations.…”
Section: Resultsmentioning
confidence: 91%